2020
DOI: 10.1101/2020.07.20.212118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staphylococcal protein A inhibits complement activation by interfering with IgG hexamer formation

Abstract: IgG molecules are essential players in the human immune response against bacterial infections. An important effector of IgG-dependent immunity is the induction of complement activation, a reaction that triggers a variety of responses that help to kill bacteria. Antibody-dependent complement activation is promoted by the organization of target-bound IgGs into hexamers that are held together via noncovalent Fc-Fc interactions. Here we show that Staphylococcal protein A (SpA), an important virulence factor and va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…In line with recent results, IgG1 and IgG3 antibodies against WTA elicit effective C3b deposition on S. aureus (Fig. 1A) 34 . Furthermore, IgG4 did not activate complement on S. aureus ( Fig.…”
Section: Igg-mediated Complement Activation Does Not Always Correlatesupporting
confidence: 92%
See 1 more Smart Citation
“…In line with recent results, IgG1 and IgG3 antibodies against WTA elicit effective C3b deposition on S. aureus (Fig. 1A) 34 . Furthermore, IgG4 did not activate complement on S. aureus ( Fig.…”
Section: Igg-mediated Complement Activation Does Not Always Correlatesupporting
confidence: 92%
“…NheI and BsiWI were used as the 3' cloning sites for VH and VL, respectively, in order to preserve the immunoglobulin heavy and kappa light chain amino acid sequence. Sequences of IgG1, IgG2, IgG3, IgG4 variable and constant heavy and light chains were previously described 51,85 (Supplemental Table 1). VH and VL sequences were derived from previously described anti-WTA GlcNAc-β-4497 (anti-WTA-4497; based on patent WO/2014/193722) 86 and anti-DNP 87 (Supplemental Table 1).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This is due to an amino acid substitution in position 435, where an histidine in IgG1, IgG2 and IgG4 becomes an arginine in most of IgG3 allotypes (19, 20). Therefore, the effector functions of IgG3 remain unaffected by the presence of SpA (21).…”
Section: Introductionmentioning
confidence: 99%
“…We and others showed that SpA protects S. aureus from phagocytic killing by binding the IgG-Fc fragment (21–23). In our previous study, we unveiled how SpA blocks IgG-mediated complement activation and subsequent killing of S. aureus (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation